Teachers and gyms at the beginnings of gymnastics in Southern Italian schools. The 1864 survey - Elia, Domenico Francesco Antonio (Rivista di Storia dell’Educazione, 2022)
This paper presents an analysis of gyms and gymnastics teachers in Southern Italy in the 1860s based on the survey conducted by the Ministry of education in 1864. On the background of national and international literature, the research aims to explore the gyms’ material conditions and the forms of teachers’ education and training. It argues that both poor equipment and low-level training affected the teaching practices of the first generation of gymnastics teachers. The paper contributes to a better understanding of regional and local features of the process of nation-building after the Unification (D’Ascenzo 2013).